Pendidikan Sains Berbasis Spiritualitas dalam Persepektif Al-Qur'an - Zamakhsyari Zamakhsyari (STIT Al-Marhalah Al-Ulya Bekasi, 2017)
Throughout 2006, Indonesia was rocked by a phenomenal work by Dr. Masaru Emoto about the true power of water. In his book entitled The True Power of Water, Emoto managed to show scientifically the results of his research that when whispered or written good words and certain prayers turn into beautiful crystals that function as